Research Advances on the Adverse Effects of Nanomaterials in a Model Organism, Caenorhabditis elegans. (22nd July 2021) - Li, Yimeng; Zhong, Lishi; Zhang, Lili; Shen, Xiaobing; Kong, Lu; Wu, Tianshu
Abstract: Along with the rapid development of nanotechnology, the biosafety assessment of nanotechnology products, including nanomaterials (NMs), has become more and more important. The nematode Caenorhabditis elegans is a valuable model organism that has been widely used in the field of biology because of its excellent advantages, including low cost, small size, short life span, and highly conservative genomes with vertebral animals. In recent years, the number of nanotoxicological researchers using C. elegans has been growing. According to these available studies, the present review classified the adverse effects of NMs in C. elegans into systematic, cellular, and molecular toxicity, and focused on summarizing and analyzing the underlying mechanisms of metal, metal oxide, and nonmetallic NMs causing toxic effects in C. elegans . Our findings provide insights into what further studies are needed to assess the biosafety of NMs in the ecosystem using C. elegans . Environ Toxicol Chem 2021;40:2406–2424. © 2021 SETAC